Determinants Of Interest In Public Accounting Careers Among Undergraduate Accounting Students: A Case Study at Upn Veteran East Java - Aprilia, Anisa; Ratnawati, Dyah (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose : This study aims to identify and analyze the factors that influence undergraduate accounting students' interest at the National Development University "Veteran" East Java in pursuing a career as a public accountant. Method: A quantitative research approach was applied. The study targeted students who had completed Audit 1 and Audit 2 courses and had internship experience. A total of 87 respondents were selected using the Slovin formula and stratified random sampling. Data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with SmartPLS 4.0 software. Results: The validity and reliability tests confirmed that all indicators met the required criteria. The model achieved a good predictive relevance (Q² = 0.622) and coefficient of determination (R² = 0.640), indicating that the model was effective in explaining variations in students’ career interest. Findings: Internship experience, academic achievement, financial rewards, and job market considerations each have a significant positive influence on students’ interest in becoming public accountants. Novelty: This study integrates expectancy theory with empirical testing using SEM-PLS in a specific institutional context, providing deeper insight into motivation-related factors in career choice among accounting students. Originality: The study contributes new empirical evidence from a developing country context, particularly focusing on UPN "Veteran" East Java, which has not been widely studied in previous research on accounting career interest. Conclusion: The research confirms that experiential, academic, economic, and market-related factors are key determinants of career interest in the public accounting profession. These insights are useful for educators, practitioners, and policymakers in designing interventions to strengthen students’ motivation toward public accounting careers. Type of Paper: Research Paper